Survival and Release Behavior of a Novel Pre-, Pro-, and Postbiotic Capsule in an In Vitro SHIME Model. (14th June 2022) - Vance, Arianne; Raut, Shilpa; Grier-Welch, Adeline; Alamdari, Nima; Sharafi, Mastaneh
Abstract: Objectives: To test the survival and release of probiotics ( Lactobacillus rhamnosus GG and Bifidobacterium animalis subsp. lactis BB-12 ), a prebiotic (bacteriophage blend), and a postbiotic (tributyrin) in a capsule-within-capsule design during passage through the gastrointestinal tract under fed and fasted conditions. Methods: Using an adapted Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) model, physiological conditions of the stomach and small intestine, including pH profiles, temperature, incubation time, and addition of bile liquid and digestive enzymes, were simulated within the same reactor over time. The capsule contents included an inner capsule, containing probiotics and prebiotic phages, and an outer capsule, containing the postbiotic, with different delivery and release characteristics. Probiotic survival was assessed via plate counts and PMA-qPCR, release of phages was assessed via phage titer assay, and tributyrin release was assessed via gas chromatography. All experiments were performed in triplicate to account for biological variability. Results: Under fasted conditions, the majority of the probiotics bypassed the stomach and small intestine in a viable form, of which more than 11 billion CFU were culturable. There were no significant differences between fasted and fed states. Similarly, the majority of the prebiotic phages survived transit through the stomach and small intestine. Tributyrin was mostly released in the small intestine. Conclusions: The capsule design ensured probiotics and prebiotic phages survived the harsh conditions of the upper gastrointestinal tract for delivery to the colon. The release of tributyrin within the small intestine supports its breakdown by pancreatic enzymes to produce short chain fatty acid butyrate. The findings of this study suggest a novel, colon-targeted probiotic delivery system explained by specific capsule and content characteristics. Funding Sources: The study was conducted by an independent lab, ProDigest, and funded and sponsored by Ritual (Natals, Inc.). Compound Solutions, Inc. also financially supported the study.